Experimental investigation of the influence of chip interference on burr height in machining micro V-grooves on electroplated copper roll die. (June 2018) - Qiao, Zheng; Qu, Da; Wang, Huiming; Wu, Dongxu; Wang, Bo
The roll-to-roll imprinting technology is considered as the most promising process for manufacturing large-area microstructured surface in a high-precision, high-efficiency and low-cost way. However, the existence of cutting burr of microstructures on roll die will deteriorate the quality of microstructures on target surface in roll-to-roll imprinting processing. For electroplated copper material, this article presents the influence of chip interference on burr in cutting process. The parameter that illustrates the level of chip interference is deduced. The influences of cutting depth and included angle of V-shaped diamond tool on burr height of V-grooves are revealed by analyzing the chip interference. A series of experiments are carried out to verify the theoretical study. The results show good agreement between theoretical derivation and experimental analysis. The reason for chip interference of cutting process is made clear. Then, the optimal process of multi-step cutting process was given as the guidance to enhance the surface quality of micro V-grooves on electroplated copper roll die. With the optimal cutting parameters, the high-quality surface of micro-prism array is achieved.